SEJARAH NABI-NABI DALAM AL-QUR’AN - Dwi Ratnasari (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2011)
In Islam, a prophet has very significant roles. Among them are as a messenger, an agent of change, and a guide to civilized society. The history of prophets in al-Qur'an is explained without any cerfain orders. They are described as revolutionary figures who guide the society from the dark age to the new thinking based on the ideology of tauhid.